Auditoria y Reporte de RSE o RSC. - Castillo Villarreal, Jorge (Revista Daena: International Journal of Good Conscience)
Corporate Social Responsibility (CSR) auditing is an essential tool to ensure that organizations meet their sustainability and social responsibility commitments. This process allows the evaluation of regulatory compliance, identification of risks and areas for improvement, and optimization of internal organizational processes. Through a structured approach, the audit provides a clear view of how business practices align with international standards such as ISO 26000 and the United Nations Global Compact. This article explores the stages of the audit process, from planning and data collection to reporting and follow-up on recommendations, highlighting the key benefits of CSR audits, including improved reputation, attracting investments, and strengthening stakeholder trust. In an increasingly sustainability-driven business environment, CSR auditing is fundamental for ensuring the long-term viability and competitiveness of organizations.